2015
DOI: 10.1186/s13550-015-0130-2
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin receptor PET/CT in restaging of typical and atypical lung carcinoids

Abstract: Background: To assess the role of somatostatin receptor (SR) PET/CT using Ga-68 DOTATOC or DOTATATE in staging and restaging of typical (TC) and atypical (AC) lung carcinoids.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Once the diagnosis is suspected, standardised characterisation of LC comprises several specific steps for evaluation that are described in Table 1 [III, B]. [4][5][6][7][8][9]18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] ThC is revealed by tumour-related symptoms, or due to functionally active tumours or by chance. [11][12][13] Diagnostic procedures, including core biopsy under ultrasonography guidance, or preferably through a thoracic computed tomography (CT) scan, or upfront surgery following the guidelines for thymic tumour diagnosis, should be carried out.…”
Section: Diagnosis and Pathology/molecular Biologymentioning
confidence: 99%
“…Once the diagnosis is suspected, standardised characterisation of LC comprises several specific steps for evaluation that are described in Table 1 [III, B]. [4][5][6][7][8][9]18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] ThC is revealed by tumour-related symptoms, or due to functionally active tumours or by chance. [11][12][13] Diagnostic procedures, including core biopsy under ultrasonography guidance, or preferably through a thoracic computed tomography (CT) scan, or upfront surgery following the guidelines for thymic tumour diagnosis, should be carried out.…”
Section: Diagnosis and Pathology/molecular Biologymentioning
confidence: 99%
“…They included proliferation ( Ki67, NAP1L1, NOL3, TECPR2 ), growth factor signaling ( ARAF, BRAF, KRAS, RAF1 ), secretion ( TPH1, VMAT1 ), epigenetic remodeling ( NAP1L1, RNF41, RSF1 ) and somatostatin receptor expression ( SSTR1, 3, 4 and 5 ). Ki-67 is well-described in BPNET [ 7 ], as is growth factor expression and signaling [ 36 ], the synthesis and transport of serotonin [ 36 ], epigenetic regulation [ 37 ] and somatostatin receptor expression [ 38 ]. It has been previously suggested that circulating levels of SSTR5 could be a potential biomarker for lung NETs [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…31 For the few studies available, a median tumor detection rate of 90% (range, 79%-100%) with Gallium-68 PET imaging of patients with lung typical/atypical carcinoids has been reported (see Supplemental Figure 2 in the online version). 10,[32][33][34][35][36][37][38][39] Use of Gallium-68 SSTRbased PET alongside 18 F-fludeoxyglucose (FDG) PET, a measure of…”
Section: Somatostatin Receptors and Sstr Imaging In Lung Typical/atypical Carcinoidsmentioning
confidence: 99%
“…Institutional guidelines should be developed and followed for possible PRRT side effects, including exacerbation of hormonal symptoms such as hypoglycemia, nausea, vomiting, and, in rare circumstances, carcinoid crisis. 32 Pericleous et al, 33 Kumar et al, 34 Jindal et al, 35 Venkitaraman et al, 10 Prasad et al, 36 Ambrosini et al, 37 Lamarca et al, 38…”
Section: Patient Statusmentioning
confidence: 99%